Automated scoring of collaterals, blood pressure, and clinical outcome after endovascular treatment in patients with acute ischemic stroke and large-vessel occlusion - Guisado-Alonso, Daniel; Camps-Renom, Pol; Delgado-Mederos, Raquel; Granell, Esther; Prats-Sánchez, Luis; Martínez-Domeño, Alejandro; Guasch-Jiménez, Marina; Acosta, M. Victoria; Ramos-Pachón, Anna; Martí-Fàbregas, Joan (Frontiers in Neurology, 2022)
Introduction We aimed to determine whether the degree of Collateral Circulation is associated with blood pressure at admission in acute ischemic stroke patients treated with endovascular treatment, and to determine its prognostic value. Methods We evaluated patients with anterior large vessel occlusion treated with endovascular treatment in a single-centre prospective registry. We collected clinical and radiological data. Automated and validated software (Brainomix Ltd., Oxford, UK) was used to generate the Collateral Score (CS) from the baseline single-phase CT angiography: 0, filling of ≤10% of the occluded MCA territory; 1, 11-50%; 2, 51-90%; 3, >90%. When dichotomized, we considered that CS was good (CS=2-3), or poor (CS=0-1). We performed bivariate and multivariable ordinal logistic regression analysis to predict CS categories in our population. The secondary outcome was to determine the influence of automated CS on functional outcome at 3 months. We defined favourable functional outcome as mRS 0-2 at 3 months. Results We included 101 patients with a mean age of 72.1 13.1 years and 57 (56.4%) of them were women. We classified patients into 4 groups according to the CS: 7 patients (6.9%) as CS=0 , 15 (14.9%) as CS=1, 43 (42.6%) as CS=2 and 36 (35.6%) as CS=3. Admission systolic blood pressure [aOR per 10 mmHg increase 0.79 (95% CI 0.68-0.92)] and higher baseline NIHSS [aOR 0.90 (95% CI, 0.84-0.96)] were associated with a worse CS. The OR of improving 1 point on the 3 month mRS was 1.63 (95% CI, 1.10 to 2.44) favouring a better CS (p= 0.016). Conclusion In acute ischemic stroke patients with anterior large vessel occlusion treated with endovascular treatment, admission systolic blood pressure was inversely associated with the automated scoring of CS on baseline CT angiography. Moreover, a good CS was associated with a favourable outcome.